Characterization and sensory evaluation of sweet bean paste using ungerminated and germinated kadyos (Cajanus cajan) seeds with varying sugar concentrations. - Mangilin, Antonette Cagbay
Sweet bean paste processing using ungerminated and germinated kadyos (Cajanus cajan) were studied for its quality and acceptability using sensory evaluation, statistical analysis, and ash and moisture content. The total production cost for sweet bean paste from ungerminated kadyos (SBPUK) and sweet bean paste from germinated kadyos (SBPGK) were also determined. Using the general acceptability test, the SBPUK and SBPGK samples of varying formulations were evaluated and showed the highest acceptability rating for formulation 1 with 50 g of sugar. The consumer preference test was conducted for the most preferred formulations (MPF) of SBPUK and SBPGK and results showed that the preferred sample for consumers with ages 18-25 years old is the commercial sweet bean paste however, for consumers ages 26 years old and above is SBPGK. Chi-square test results have shown that the age of consumers does not influence their preferences in choosing their preferred sample among the control, ungerminated, and germinated samples. Moreover, the ANOVA and Tukey test showed that there is a significant difference in the means of the ungerminated and germinated treatments with two varying formulations in terms of taste and general acceptability. On the other hand, for ash and moisture content, results showed that the ash content is higher for SBPUK while the moisture content in SBPGK is higher. The chi-square test results for ash and moisture content have shown that the ungerminated and germinated treatments do not influence the ash and moisture content of the sweet bean paste. Lastly, the production cost of SBPUK and SBPGK were determined using the principle of material balance and results have shown that the production cost for SBPGK is PhP 316.46, which is greater than that of SBPUK with a production cost of PhP 162.95.